SARS-CoV-2 nsp13, nsp14, nsp15 and orf6 function as potent interferon antagonists. Issue 1 (1st January 2020) - Yuen, Chun-Kit; Lam, Joy-Yan; Wong, Wan-Man; Mak, Long-Fung; Wang, Xiaohui; Chu, Hin; Cai, Jian-Piao; Jin, Dong-Yan; To, Kelvin Kai-Wang; Chan, Jasper Fuk-Woo; Yuen, Kwok-Yung; Kok, Kin-Hang
ABSTRACT: The Coronavirus disease 2019 (COVID-19), which is caused by the novel SARS-CoV-2 virus, is now causing a tremendous global health concern. Since its first appearance in December 2019, the outbreak has already caused over 5.8 million infections worldwide (till 29 May 2020), with more than 0.35 million deaths. Early virus-mediated immune suppression is believed to be one of the unique characteristics of SARS-CoV-2 infection and contributes at least partially to the viral pathogenesis. In this study, we identified the key viral interferon antagonists of SARS-CoV-2 and compared them with two well-characterized SARS-CoV interferon antagonists, PLpro and orf6. Here we demonstrated that the SARS-CoV-2 nsp13, nsp14, nsp15 and orf6, but not the unique orf8, could potently suppress primary interferon production and interferon signalling. Although SARS-CoV PLpro has been well-characterized for its potent interferon-antagonizing, deubiquitinase and protease activities, SARS-CoV-2 PLpro, despite sharing high amino acid sequence similarity with SARS-CoV, loses both interferon-antagonising and deubiquitinase activities. Among the 27 viral proteins, SARS-CoV-2 orf6 demonstrated the strongest suppression on both primary interferon production and interferon signalling. Orf6-deleted SARS-CoV-2 may be considered for the development of intranasal live-but-attenuated vaccine against COVID-19.